Prosedur Sistem Penataan Arsip di Program Studi Administrasi Bisnis Jurusan Administrasi Bisnis Politeknik Negeri Manado - Jufrina Mandulangi; Deky E. Wibowo Mundung (Syntax Idea, 1919)
The business administration study program is one part of the Business administration Department owned by the Vocational education institution at the Manado State Polytechnic, established in 1987 and aims to produce student graduates who are able to carry out functions as an administrative staff professionally in accordance with their field of expertise. As well as being able to complete administrative tasks in a relatively short time which is supported by the ability to use language, the latest technology and supported by high morals, responsibility and discipline. In carrying out the activity process has benchmarks that must be achieved in improving quality, one of which is by always producing good quality archives and at certain times it is needed for smooth activities in the Business administration study program. For this reason, the resulting archive must be managed according to the procedures used and then stored and can be found quickly and precisely when needed. The role of archives as a support for the organization in the smooth implementation of activities in accordance with its management procedures. In fact, it was found when the initial observation was made that there was a lack of complete documents manually or electronically, there was no special officer to handle the management of archives, so that when needed it was very difficult to find. A number of documents or archives available are not well organized due to the availability of equipment that is still minimal. This research was conducted with the aim that the availability of documents and a number of documents can be well organized and protected, archives can be well organized with the availability of equipment and special officers who handle it. This research will use qualitative research methods by collecting data through observation, interviews and documentation.